GASTROPOD COMMUNITY STRUCTURE in the WATERS of GANGGA SATU VILLAGE, WEST LIKUPANG, NORTH MINAHASA - Klaudio Mauli; Alex D Kambey; Ruddy D Moningkey; Nego E Bataragoa; Jety K Rangan; Medy Ompi (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2022)
This study aims to determine the types and community structures of gastropods in the waters of Gangga Satu Village, West Likupang, North Minahasa. Data were collected using the line transect quadratic method, with a transect length of 100 m and a square measure of 1 m x 1 m. Gastropod species in the southern waters of Gangga Satu village, West Likupang, North Minahasa consist of 18 species (11 genera), 5 families, and 4 orders.  namely Thais tuberosa, Morula rumphius, Nassarius distorus, Nassarius albescens, Mitra litterata, Mitra paupercula, Conus parvulus, Conus striatus, Conus Chaldeaus, Engina mendicaria, Nerita undata, Nerita plicata, Nerita polita, Clypeomorus cerithium acina, Turbo bruneus. Density of all species K = 4.76, relative density of 13% in Morula rumphius species, diversity of H' = 1.18 and dominance of C = 0.07Keywords: Community structur; Gastropod AbstrakPenelitian ini bertujuan untuk mengetahui jenis-jenis dan struktur komunitas gastropoda di Perairan Desa Gangga Satu Likupang Barat Minahasa Utara. Pengambilan data menggunakan metode line transek kuadrat , dengan panjang transek 100 m dan ukuran kuadrat 1m x 1m. Jenis Gastropoda  di perairan selatan desa Gangga Satu, Likupang Barat, Minahasa Utara terdiri dari 18 spesies (11 genus), 5 famili, dan 4 ordo  yakni Thais tuberosa, Morula rumphius, Nassarius distorus, Nassarius albescens, Mitra litterata, Mitra paupercula, Conus parvulus, Conus striatus, Conus Chaldeaus, Engina mendicaria, Nerita undata, Nerita plicata, Nerita polita, Clypeomorus bifasciata, Cerithium atratum, Lunela cineria, Turbo bruneus. Kepadatan seluru spesies K= 4,76, kepadatan relatif sebesar 13% pada spesies Morula rumphius, keanekaragaman H’= 1,18 dan dominasi C= 0,07Kata kunci:Strukturkomunitas; Gastropoda